2003
DOI: 10.1086/379126
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Hemophagocytic Lymphohistiocytosis Associated with Epstein-Barr Virus Infection in a Patient with a Novel Mutation in the Signaling Lymphocytic Activation Molecule--Associated Protein

Abstract: Individuals with X-linked lymphoproliferative disease are susceptible to severe Epstein-Barr virus (EBV) infections that are often fatal. Mutations in signaling lymphocytic activation molecule-associated protein (SAP) are associated with this illness. We describe a patient with a novel serine-to-proline mutation at aa 57 in SAP and compare the location of the altered amino acid with all known missense mutations in the SAP-encoding SH2D1A gene, including those of 4 additional individuals whose cases have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…4 EBV, a DNA (deoxyribonucleic acid) virus and member of the Herpesviridae family has been the most consistently reported virus associated with HLH. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The majority of EBV-associated HLH cases have been reported in Asia, with limited information on the incidence elsewhere in the world. A Japanese study estimated the annual incidence of HLH at 1 in 800,000 persons per year, with 90% of these cases being secondary and one-third of these secondary cases being related to EBV.…”
Section: Infectionsmentioning
confidence: 99%
“…4 EBV, a DNA (deoxyribonucleic acid) virus and member of the Herpesviridae family has been the most consistently reported virus associated with HLH. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The majority of EBV-associated HLH cases have been reported in Asia, with limited information on the incidence elsewhere in the world. A Japanese study estimated the annual incidence of HLH at 1 in 800,000 persons per year, with 90% of these cases being secondary and one-third of these secondary cases being related to EBV.…”
Section: Infectionsmentioning
confidence: 99%
“…To our knowledge only 13 well‐characterized cases of EBV‐associated HLH have been described in the United States (Supplemental Table III) [Quintanilla‐Martinez et al, 2000; Halasa et al, 2003; Lindemann and Greene, 2005; Mischler et al, 2007; Rouphael et al, 2007; Brodkin et al, 2008; Kaza et al, 2008; Belyea et al, 2010], and of these, four (30.8%) were Latino [Quintanilla‐Martinez et al, 2000; Brodkin et al, 2008], four (30.8%) white [Quintanilla‐Martinez et al, 2000; Halasa et al, 2003; Mischler et al, 2007; Rouphael et al, 2007], one (7.7%) Asian [Quintanilla‐Martinez et al, 2000], and one (7.7%) African‐American [Kaza et al, 2008]. Race/ethnicity was not reported in three (23.1%) of the cases [Lindemann and Greene, 2005; Belyea et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Race/ethnicity was not reported in three (23.1%) of the cases [Lindemann and Greene, 2005; Belyea et al, 2010]. In four (30.8%) of these cases another cause, such as immunodeficiency [Halasa et al, 2003; Mischler et al, 2007; Kaza et al, 2008] or malignancy [Brodkin et al, 2008] was attributed as the primary cause of HLH. A seasonal pattern has been suggested for EBV‐HLH, with cases more often occurring in the summer [Chen et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Epstein-Barr virus (EBV), a DNA virus and member of the Herpesviridae family, has been consistently associated with HLH. [5][6][7][8][9][10][11][12][13][14][15] HLH in children is a rare disease with a high fatality rate. Studies have shown that most cytokines related to HLH are activated through activation of the Janus Kinase (JAK)/signal transducer and activator of transcription signaling pathway, which not only regulates the biological activity of cytokines, but also affects the differentiation of primary T cells into T helper (TH) cell families, TH1, TH2, TH17, and regulatory T cells.…”
Section: Introductionmentioning
confidence: 99%